2023
DOI: 10.3390/met13040728
|View full text |Cite
|
Sign up to set email alerts
|

Meta-GGA SCAN Functional in the Prediction of Ground State Properties of Magnetic Materials: Review of the Current State

Abstract: In this review, we consider state-of-the-art density functional theory (DFT) investigations of strongly correlated systems performed with the meta-generalized gradient approximation (meta-GGA) strongly constrained and appropriately normed (SCAN) functional during the last five years. The study of such systems in the framework of the DFT is complicated because the well-known exchange–correlation functionals of the local density approximation (LDA) and generalized gradient approximation (GGA) families are not de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 170 publications
0
1
0
Order By: Relevance
“…Computational modeling of these systems with satisfactory accuracy and computational efficiency is feasible with a semilocal density functional such as strongly constrained and appropriately normed (SCAN) meta-GGA functionals. It has been reported by several research groups that the recently developed meta-GGA functionals, in particular, the SCAN functional performs quite well, similar to and even in some cases better than the HSE-06 functional. They have demonstrated that the meta-GGA SCAN functional is applied to many different systems, like perovskites, 2D materials, wide bandgap oxide materials, donor and acceptor impurities in group-IV semiconductors, insulators, topological insulators, and alloys, to understand the properties of the material like mechanical, vibrational, optical, magnetic, structural, large bandgap optical phonons, elastic constants, electronics, photocathode, photocatalytic water splitting, etc. In this study, we have tested the efficacy of the SCAN meta-GGA functional in analyzing the electronic properties of vdW-layered materials, with the C 2 N/MoS 2 heterostructure serving as a prototype.…”
Section: Introductionmentioning
confidence: 99%
“…Computational modeling of these systems with satisfactory accuracy and computational efficiency is feasible with a semilocal density functional such as strongly constrained and appropriately normed (SCAN) meta-GGA functionals. It has been reported by several research groups that the recently developed meta-GGA functionals, in particular, the SCAN functional performs quite well, similar to and even in some cases better than the HSE-06 functional. They have demonstrated that the meta-GGA SCAN functional is applied to many different systems, like perovskites, 2D materials, wide bandgap oxide materials, donor and acceptor impurities in group-IV semiconductors, insulators, topological insulators, and alloys, to understand the properties of the material like mechanical, vibrational, optical, magnetic, structural, large bandgap optical phonons, elastic constants, electronics, photocathode, photocatalytic water splitting, etc. In this study, we have tested the efficacy of the SCAN meta-GGA functional in analyzing the electronic properties of vdW-layered materials, with the C 2 N/MoS 2 heterostructure serving as a prototype.…”
Section: Introductionmentioning
confidence: 99%